Funcionalidad y eficacia del Plan Esperanza en mujeres con cáncer de mama en el Instituto Nacional de Enfermedades Neoplásicas, Lima 2022-2023 - Angulo Fernández, Ruth Lilibeth (2024)
The study examined the functionality and effectiveness of the Plan Esperanza in women with breast cancer treated at the National Institute of Neoplastic Diseases in Peru. This analysis is crucial for understanding how the plan addresses the challenges of cancer, especially in disadvantaged populations, and how it can be improved to provide more effective care. The study investigated disparities in receiving healthcare and their impact on early diagnosis and mortality from breast cancer among different demographic groups. Additionally, the economic impact on the quality of life of women with breast cancer was evaluated. The research explored the role of Social Management in social policies and programs related to breast cancer. Key aspects such as the budgeting of the "Plan Esperanza," its focus on poverty, and priority programming were identified. Furthermore, the analysis included how these decisions affect the comprehensive care of patients. Using a qualitative approach that included 17 interviews, 2 focus groups, a historical perspective, and document review, a deep understanding of the situation and the perspectives of the various stakeholders involved was obtained. A total of 36 variables related to healthcare were analyzed. This type of research is essential for improving healthcare services and patient support, identifying areas for improvement and opportunities to strengthen the program. Additionally, it contributes to informed decision-making in resource allocation and health policies, allowing for a more effective approach to addressing the disease.